Handbook of Megachurches - Hunt, Stephen (Brill, 2020)
This innovating edited volume provides a broad but detailed overview of a relatively recent significant development in church organisation, the megachurch. Its aim is to capture empirically and theoretically the megachurch phenomenon as a unique form of religious expression through author contributions from several academic disciplines including the Sociology of Religion, Religious Studies, Church History and Theology.
Description based on print version record.
KU Select 2019: HSS Frontlist Books
Keywords: Religion; Religion; Electronic books